The Effect of GIBBS Factor on Transient Analysis in Underground Power Cables - Yılmaz Uyaroglu; Selcuk Emiroglu (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In thiswork, the transient over – voltage phenomena occurred at 34.5 kV AC undergroundcable transmission systems during the closure of the underground cables is tobe studied and simulated by using MATLAB program. Then, the transient voltageoccurred at the underground cables is analyzed by using modified Fouriertransform. The studied systems of underground cables are firstly modeled infrequency domain. Transient voltages induced at the sending-end and receiving-endterminals of an underground cable of transmission system are calculated infrequency domain and using inverse Fourier Transform, the sending end and receivingend voltages are obtained by converting to time domain. The effects of cablelength and source impedance on transient over – voltage phenomena atunderground cables are investigated. Also, the effects of GIBBS factor intransients are researched in order to eliminate GIBBS oscillations. Numericalsimulations are presented to demonstrate the transient voltages induced at theterminals of sending-end and receiving-end of an underground cable attransmission system and the effects of GIBBS factor.